NAVIGATING THE LEGAL LANDSCAPE OF DIGITAL OBJECTS IN SOCIAL MEDIA: A CIVIL LAW PERSPECTIVE (World Bulletin of Management and Law, 2023)
This article examines the civil law aspects of social networks, focusing on the objects of relations, including social networks, accounts (profiles), methods (tangible or virtual property), digital asset status, information, and the distinction between simple and complex objects. The study highlights the difficulties in defining the legal nature associated with various digital assets and virtual property in the context of social networks. The article examines the work of various authors, highlighting the need for a comprehensive legal framework to ensure the effective management of academic social networks, contributing to the harmonization of regulations and policies in the digital sphere.